1951
DOI: 10.3133/pp226
|View full text |Cite
|
Sign up to set email alerts
|

The geology and geography of the Paunsaugunt region, Utah

Abstract: Page 42 19. Diagrams showing features of the Cretaceous and Tertiary formations at their contact_______________________ 44 20. Basal conglomerate of the Wasatch formation in contact with sandstone of the Kaiparowits formation_________ 45 21. Characteristic erosion features in the massive limestone along the Tropic traiL_____________________________ 47 22. White upper conglomeratic part of the Wasatch formation in Castle Wash_________________________________ 48 23. Conglomerate interbedded with pink limestone, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1954
1954
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…The positions of such geographic features may be found in the quadrangle maps of Utah and in the publications of Baker, Dane, and Reeside (1936); Gilluly (1929); Gregory (1950Gregory ( , 1951; Hardy (1952aHardy ( , 1962and Spieker (1946).…”
Section: Introductionmentioning
confidence: 99%
“…The positions of such geographic features may be found in the quadrangle maps of Utah and in the publications of Baker, Dane, and Reeside (1936); Gilluly (1929); Gregory (1950Gregory ( , 1951; Hardy (1952aHardy ( , 1962and Spieker (1946).…”
Section: Introductionmentioning
confidence: 99%
“…1). Displacement along the Sevier fault, in the western part of the study area, varies from less than 100 to as much as 2,000 ft (Gregory, 1951). Displacement generally decreases from south to north, and is 2,000 ft in Yellow Jacket Canyon, from 1,000 to 2,000 ft between Mt.…”
Section: Faults and Fracturingmentioning
confidence: 93%
“…The hydrologic system of the Navajo Sandstone in the study area has been investigated by the State of Utah, the U.S. Geological Survey, coal company hydrologists, and private consultants, and several aspects of hydrologic properties and ground-water movement have been discussed in the reports resulting from these studies. Reports of particular interest to this investigation include those by Bingham Engineering (1973, 1974, 1979, 1981a, 1981b, and 1987); Blanchard (1986); ; Doelling and Graham (1972); Peltis (1966); Goode (1964; Gregory (1951); Hintze (1963); Sandberg (1979); and Todd (1987), because they contain most of the historic geologic and hydrologic data for the area. Hie reports by Bingham Engineering include descriptions of the hydrology, geology, and drilling program in the Navajo Sandstone conducted by the coal company.…”
Section: Previous Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The age of the Claron is poorly constrained, and because of the incidence of rare invertebrate fossils (Gregory, 1951) that suggested that lower parts are Eocene, we previously considered the formation to be Eocene and Oligocene . Goldstrand (1990), however, noted that palynomorph fossils in samples from basal Claron rocks from the eastern Pine Valley Mountains indicate a late Paleocene age for these rocks, whereas a fission-track date of 50±6 Ma that he determined from rocks collected just below the Claron contact in the Table Cliff Plateau indicates that there the basal Claron is Eocene.…”
Section: Lower Cenozoic Sedimentary Sequence Claron Formation and Relmentioning
confidence: 99%